Северомесопотамский город в конце XIX-первой половине XVIII в до н.э. по текстам из Мари (Краткое сообщение) - Грибов, P. A. (1973)
Gribov, R. А.; The city of Northern Mesopotamia in the late 19th and the first half of the 18th centuries B.C. according to the texts from Mari (Short communication); engl. Résumé S. 219.